Women For: Ballot Reccomendations (1976)
This 1976 advisory ballot from WOMEN FOR: provides endorsed candidates and ballot measure recommendations for the June 8 election. The organization takes no stand on the presidential and U.S. Senate races but endorses selected candidates for Congress, State Senate, and State Assembly, including Jane Tolmach in the 36th District. It also supports John Van de Kamp for District Attorney, specific judicial candidates, state measures 1–15 (Yes), county measures A and B (Yes), special district measures R and T (Yes), and opposes Los Angeles City Measure C. The pamphlet encourages voters to bring the advisory ballot to the polls and invites membership contributions to support voter education efforts.